Pengembangan Potensi Desa Kanigoro Melalui Wisata Pantai Pringjono Serta Penyuluhan Tentang Covid-19 - Kristiawan, Yanuarius Benny (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Kanigoro Village is a village that has a lot of beauty, but unfortunately, these beauties are still not exposed. For this reason, the compilers agreed to do two types of work programs in Kanigoro Village; Village Potentials and Pocket Books. Regarding the potential of the village, the compilers choose Pringjono Beach because this beach can be a characteristic of Kanigoro Village. Then the compilers also choose to make a Pocketbook about Covid-19 because the Covid-19 pandemic is still a trend in Indonesia and the world. The purpose of this activity is to provide knowledge of village potential that can be utilized especially in the Kanigoro Village and provide knowledge and understanding of the Covid-19 pandemic which is currently a hot topic. The method that the compilers do is to observe village data through the village website and other information related through news or other official websites. The result of these activities is that Pringjono Beach as the potential of Kanigoro Village expected to advance Kanigoro Village of income and image village. In addition, through the pocketbook “Smart Against Covid-19”, the people of Kanigoro Village also have a proper understanding of the Covid-19 virus, especially the dangers, prevention, and handling.